Prospects of the technology of joint combustion of biomass and coal at energy facilities - E. S. Dremicheva; E. R. Zvereva; F. I. Burganova; L. O. Zverev (Известия высших учебных заведений: Проблемы энергетики)
TARGET. PURPOSE. Bioenergy is aimed at the production of biological fuels, alternative to natural fossil fuels. Biofuel is obtained from plant or animal raw materials, from the waste products of organisms, from industrial waste, from agricultural waste, etc. The article studies the properties of coal from the Kuznetsk Basin with solid fuel compositions from local fuels and organic waste (biomass), as well as the possibility of their co-combustion in boilers of low and medium power. METHODS. To solve the set tasks in the scientific article, a computational and empirical research method was used - experiment. Experimental studies were carried out in the laboratories of the Department of Technologies in Energy and Oil and Gas Processing of the Kazan State Power Engineering University, in the laboratories of the Kazan CHP-1 branch of Tatenergo and the Kazan CHP-3 branch of TKG-16. As objects of research were selected: coal of the Kuznetsk coal basin; peat from the Sosnovoye deposit of the Republic of Tatarstan; sawdust obtained after processing deciduous trees; cake from processed oilseeds at Kazan Oil Extraction Plant JSC. In accordance with the current GOST, humidity (GOST R 52911-2013), ash content (GOST R 55661-2013), and the yield of volatile substances (GOST R 55661-2013) of fuel samples were determined. The results of calculated and experimental studies on the heat of combustion are presented; ash content, the release of volatile products in the composition of fuels when they are co-fired. The saving of natural fuel and the prevented environmental damage to the atmosphere and soil during co-combustion of solid fuel compositions are calculated. A scheme has been developed for co-firing coal and biomass with subsequent complex purification of the resulting harmful gases by the ozone-ammonia method. CONCLUSION. Peat and sawdust, having a sufficiently high calorific value and low ash content, are a promising fuel, when combusted with coal, for boilers of low and medium power in areas with low gasification. The use of local fuel resources, alternative fuels will reduce the consumption of natural fossil fuels, increase the environmental safety of enterprises in the fuel and energy complex, small-scale energy, and ensure a sustainable growth of the gross national product.